Arming without aiming : India's military modernization - Cohen, Stephen P., 1936-; Dasgupta, Sunil (Washington, D.C. : Brookings Institution Press, 2010)
'India, a leading importer of advance conventional weaponry, has not planned strategically for its military needs, although the haphazard approach, due to competing elements within the military and a restraint policy in place since the Nehru era, may be the right one in seeking accommodation with others in the region'--Provided by publisher
Includes bibliographical references and index.
Keywords: India -- Armed Forces -- Weapons systems; India -- Armed Forces -- Operational readiness; India -- Defenses; India -- Military policy